Hydrogel-encapsulated red vine leaf phenolics and their impact on dicarbonyl compounds in gluten-free muffins - Aldemir, Serap; Ozgolet, Muhammed; Karasu, Salih; Arici, Muhammet (TAYLOR & FRANCIS LTD, 2026)
This study investigated the effects of encapsulating red vine leaf phenolics (Royal, Black Kismis, Spil Karasi) in flaxseed gum (FG) hydrogels on gluten-free muffins quality and dicarbonyl compounds. FG hydrogels enhanced batter viscoelasticity and consistency (K: 1107.04-1550.59 Pa center dot s(n)), while phenolic addition reduced post-shear recovery from 29.3% to 18.9%-25.5%. Phenolic-enriched muffins showed higher TPC (4.41-5.34 mg GAE/g DM), antioxidant capacity (DPPH: 0.92-1.69 mg TE/g DM; CUPRAC: 2.88-3.97 mu mol TE/g DM), and oxidative stability (IP: 592.5-674.5 vs. 508.0-529.5 min), alongside increased hardness (up to 39.95 N at day 7) but reduced cohesiveness and resilience. Dicarbonyl levels were significantly lower in phenolic-enriched muffins (GO: 391.85-450.63; MGO: 134.10-140.20 mu g/100 g) than in FG controls (GO: 580.19; MGO: 155.11 mu g/100 g), indicating effective inhibition of dicarbonyl compounds. Despite minor losses in flavor and sweetness scores due to intrinsic bitterness, hydrogel encapsulation successfully retained bioactive components while improving functional muffin quality.
Keywords: Dicarbonyl compounds; encapsulation; gluten-free muffin; hydrogel; red vine leaf phenolics; OXIDATIVE STABILITY; BAKERY PRODUCTS; QUALITY; POLYPHENOL; HYDROCOLLOIDS; ANTIOXIDANTS; CAPACITY; MULBERRY; STRESS; STARCH; Food Science & Technology